Internalisasi Nilai Ahlu Sunnah Wal Jama’ah An-Nahdliyah dalam Kurikulum Program Studi Pendidikan Agama Islam Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdlatul Ulama Indonesia - Hanafiah; Rahman, M. Abd.; Bahri, Saiful; Hayaturrohman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find patterns in the internalization process of Ahlu Sunnah wal Jama'ah An-Nahdliyah values in the curriculum of the Islamic Education Study Program at the Faculty of Teacher Training and Education, Nahdlatul Ulama Indonesia University. Using a qualitative approach, this research explores how these values are internalized in the development of courses and implemented in students' academic lives. Data were collected through interviews, observations, and document analysis. The results of this research reveal a pattern of internalization of Ahlu Sunnah wal Jama’ah An-Nahdliyah values, with three stages of internalization identified. Firstly, by incorporating these values as learning outcomes. Secondly, in the implementation stage by including courses that intersect with these values, not only through the written curriculum but also through the hidden curriculum as a support for materials obtained in lectures. Additionally, these values are transmitted through relevant activities, such as seminars strengthening the Pancasila ideology. Evaluation of students' understanding of these values is conducted through mid-term exams, final exams, and thesis defense sessions (munaqasyah).